2007
DOI: 10.1103/physreve.76.026319
|View full text |Cite|
|
Sign up to set email alerts
|

Physics of reshock and mixing in single-mode Richtmyer-Meshkov instability

Abstract: The ninth-order weighted essentially nonoscillatory ͑WENO͒ shock-capturing method is used to investigate the physics of reshock and mixing in two-dimensional single-mode Richtmyer-Meshkov instability to late times. The initial conditions and computational domain were adapted from the Mach 1.21 air ͑acetone͒/SF 6 shock tube experiment of Collins and Jacobs ͓J. Fluid Mech. 464, 113 ͑2002͔͒: the growth of the bubble and spike amplitudes from fifth-and ninth-order WENO simulations of this experiment were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 49 publications
3
48
0
2
Order By: Relevance
“…This effect is particularly visible at high A > 0. This suggests that the expansion waves have a segregating role in the evolution of the mixing zone, where two mixing sub-regions would coexist, as Schilling et al (2007) observed in their two-dimensional light-heavy simulations.…”
Section: Turbulent Kinetic Energy and Dissipationmentioning
confidence: 68%
See 2 more Smart Citations
“…This effect is particularly visible at high A > 0. This suggests that the expansion waves have a segregating role in the evolution of the mixing zone, where two mixing sub-regions would coexist, as Schilling et al (2007) observed in their two-dimensional light-heavy simulations.…”
Section: Turbulent Kinetic Energy and Dissipationmentioning
confidence: 68%
“…These simulations reproduce some of the observations of Collins & Jacobs (2002) obtained from membrane-free shock tube experiments on the RMI at a light-heavy (air (acetone)-SF 6 , A ≈ 0.60) single-mode interface impacted by a Mach 1.21 shock. Schilling et al (2007) compare the simulated mixing-layer amplitude with existing reshock models evaluated at the same Atwood ratio (Mikaelian 1989;Brouillette & Sturtevant 1994;Charakhchyan 2001) during the post-reshock/preexpansion phase. Lacking complications present in experimental studies, both Schilling et al (2007) and Hill et al (2006) were able to examine the flow evolution over a wider time period following reshock than is customarily reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this model describes three-dimensional multimode interfaces, it has been shown previously to provide a good estimate of amplitude growth of single mode interfaces after reshock [13].…”
Section: Model Comparisonmentioning
confidence: 99%
“…Accordingly, the effect of viscosity was considerably underestimated in many Richtmyer-Meshkov investigations that solved only the Euler equations 13,14,17,18 or solved the Euler equations and additionally neglected compressibility effects [30][31][32] assuming a constant ratio of specific heats for all fluids involved. Fig.…”
mentioning
confidence: 99%